(D2-2D+3)y=x2-1
"(D^2 - 2D +3) y = x^2 - 1"
The differential equation can be written as
"y'' - 2y' +3y = x^2 -1"
The auxiliary equation of the homogenous part is
"m^2-2m+3 = 0"
Solving the quadratic equation, we have that
"m = 1 \\pm \\sqrt{2}i"
Hence the solution of the homogenous part is
"y = e^x(c_1\\cos \\sqrt{2}x + i \\,c_2\\sin \\sqrt{2}x)"
We use the method of undetermined coefficient to solve the other part.
Suppose
"y = ax^2 + bx + c"
Then
"y' = 2ax + b"
"y'' = 2a"
Substituting into the given differential equation, we have
"2a-2(2ax+b)+3(ax^2+bx+c) = x^2 - 1"
Comparing the coefficients of "x^2" we have
"3a = 1 \\implies a = \\dfrac{1}{3}"
Comparing the coefficients of x, we have
"-4a +3b = 0 \\implies b = \\dfrac{4}{9}"
Comparing the constants, we have"2a -2b+3c = -1 \\implies c = - \\dfrac{7}{27}"
Hence, we have that the solution for this part is "y= \\frac{1}{3}x^2 + \\frac{4}{9}x - \\frac{7}{27}"
So the general solution is
"y = e^x(c_1\\cos \\sqrt{2}x + i \\,c_2\\sin \\sqrt{2}x) +\\frac{1}{3}x^2 + \\frac{4}{9}x - \\frac{7}{27}"
Comments
Dear Nshalati, please submit a new question and describe all requirements to avoid any misunderstanding.
Thank you. Can you solve it using the D-operator method?
Leave a comment